Transaminase triggered aza-Michael approach for the enantioselective synthesis of piperidine scaffolds - Ryan, James; Šiaučiulis, Mindaugas; Gomm, Andrew; Macia, Beatriz; O'Reilly, Elaine; Caprio, Vittorio (American Chemical Society, 2016)
The expanding “toolbox” of biocatalysts opens new opportunities to redesign synthetic strategies to target molecules by incorporating a key enzymatic step into the synthesis. Herein, we describe a general biocatalytic approach for the enantioselective preparation of 2,6-disubstituted piperidines starting from easily accessible pro-chiral ketoenones. The strategy represents a new biocatalytic disconnection, which relies on an ω-TA-mediated aza-Michael reaction. Significantly, we show that the reversible enzymatic process can power the shuttling of amine functionality across a molecular framework, providing access to the desired aza-Michael products.